Eletronarcose em tilápias do Nilo (Oreochromis niloticus) e qualidade do filé - Silva, Deividy Miranda Lima da (2016)
The objective of the present study was to verify the application of eletronarcosis in Nile tilapias (Oreochromis niloticus), to obtain a humanitary slaughter and a higher stunning time, keeping the steak characteristics. It was tested the tima of exposition (5, 10, 20 and 30 seconds s) of the fish in different electric currents (1,5 3,0, 4,5 and 6,0 Amperes A) and in two tipes of tension (Alternating current AC and Direct current DC). For this, a total of 184 copies of tilapia weighting 247,08 ± 37,04g and length of 23,93 ± 1,09cm were used. In the first study it was used 128 fish, that were individually stunned, using a tension regulator (VARIAC), in which was connected two aluminum electrodes, that stayed immersed in a plastic box with water and the pre-determined time of exposition were controlled in a manual way. All the fish were filmed and later it was verified through the videos how much time each individual to return the behavioral reflexes (Opercular Rate OR, Swimming SW and Balance BA). The second study analyzed variables corresponding to the cold steak quality, using the quality index method (QIM) and the pH in each 72 hours for 36 days, and the steak color was measured only on day 0. The steaks were obtained from tilapias stunned by eletronarcosis (AC 3 and 6A and DC 3A, with time of exposition of the fish for 30s) and ice was the control method. It was verified significant differences (p < 0,05) in both studies, being the higher stunning time with the use of AC from 3 to 6A for 30s where the final return of spontaneous behaviors was from 179 to 360s to the BA, the OR was the first to be manifested after the stunning, with the time of returning from 37 to 46s and between this there was the swimming return, with time from 140 to 154s. For the analyzed variables of the steak, it was obtained influence on pH due to the interaction time*treatment, which grew over the days of analysis, and reaching level of rejection from day 15, as well as the scores of quality index (QI) parameters, in this it was verified high correlation between the time of storage and QI, with R² between 0,94 and 0,96, but with medium QI different (p < 0,05) to AC 6A. And color did not differ (p < 0,05) between the stunning methods, showing that the eletronarcosis can be applied, using AC from 3 to 6A for 30s, and having time to perform euthanasia between 37 and 46s.